2017
DOI: 10.1002/ab.21716
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the early stages of social information processing for adolescents involved in bullying

Abstract: Bullying victimization has commonly been associated with deficiencies in social information processing (SIP). In contrast, findings regarding bullying perpetration are mixed, with some researchers claiming that bullies may have superior SIP abilities than victimized or uninvolved youth. This study investigated the effects of bullying and victimization on early SIP; specifically the recognition and interpretation of social information. In stage 1, 2,782 adolescents (11-16 years) were screened for bullying invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 71 publications
(123 reference statements)
3
37
1
Order By: Relevance
“…In contrast, in Germany, bullies were as socially supported and personally resilient but even more self-efficient than those not involved in any bullying. This is consistent with previous findings that bullying is little socially sanctioned and conducted by students who are competent social manipulators with good emotional well-being (e.g., 5,6,58,59).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, in Germany, bullies were as socially supported and personally resilient but even more self-efficient than those not involved in any bullying. This is consistent with previous findings that bullying is little socially sanctioned and conducted by students who are competent social manipulators with good emotional well-being (e.g., 5,6,58,59).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies investigating the relationship between bullying involvement and the ability to recognize facial emotion have focused primarily on adolescents with typical neurodevelopment rather than adolescents with ASD. Most of these studies on general children and adolescents have discovered that victims had a lower ability to correctly recognize others' facial emotions [43,44]; however, research has found no significant difference in emotion recognition abilities between bullying perpetrators and neutrals [45,46]. Pozzoli et al [44] studied adolescents with typical neurodevelopment and observed that bullying perpetrators were more likely to correctly recognize others' emotion of fear than nonperpetrators did, allowing them to more efficaciously perform aggressive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported bullying was based on the Bullying and Friendship Interview schedule (Wolke, Woods, Bloomfield, & Karstadt, 2000), a validated measure of bullying behaviour (Griffiths et al, 2006;Schreier et al, 2009). The scale included 13 behavioural descriptions (Wolke, Lee, & Guy, 2017) and assessed three different types of bullying, i.e., direct (e.g., "been hit or beaten up"), relational (e.g., "had lies / nasty things spread about you") and cyber (e.g. "had embarrassing pictures posted online without permission").…”
Section: Methodsmentioning
confidence: 99%